Ad-hoc percutaneous coronary intervention and staged percutaneous coronary intervention. - Rahman, Z; Paul, GK; Choudhury, AK (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):757-65 The abstract of this article is available on the PubMed website